Coping with long-COVID stigma: The role of self-compassion and self-coldness - Maor Shani; Kilian Wübbelt (Health Psychology Open, 2025)
Long COVID has been associated with stigmatization, prompting exploration of coping mechanisms. This cross-sectional study examined whether self-compassion and self-coldness mediate long-COVID stigma’s effects on well-being. We surveyed 201 German adults with long-COVID (89% female; M age = 43.27, SD = 10.57). Most were officially diagnosed (88%), and 93% still experienced long-COVID symptoms at the time of survey. Measures included stigma, self-compassion, self-coldness, subjective well-being (SWB), and flourishing. Long-COVID stigma negatively correlated with SWB and flourishing. Higher self-compassion and lower self-coldness predicted better outcomes. Internalized stigma predicted lower flourishing through decreased self-compassion and increased self-coldness. In contrast, enacted stigma was associated with higher SWB and flourishing through lower self-coldness. Overall, mediation effects via self-coldness were significantly stronger than those via self-compassion, particularly in flourishing. These findings highlight the interplay between stigma, self-relating, and well-being, indicating both adaptive and maladaptive pathways. Interventions promoting self-compassion and reducing self-coldness may support holistic long-COVID care.